AN INCIDENTAL DUMBBELL PRANG?. Issue 12 (15th November 2016) - Moloney, Patrick; Bradley, Maeve; Maloney, Eimear; Riordan, Sean O'; Connolly, Sean; McGuigan, Christopher
Abstract : Introduction: Bifacial weakness with paraesthesias is a rare variant of Guillan- Barré syndrome (GBS) defined by rapidly progressive facial diplegia and distal limb paraesthesias. Case History: A 32-year-old man developed sudden onset, symmetric paraesthesias of his fingertips after dropping a 60 kg dumbbell onto his neck. That night he developed lower back pain and 5 days later noticed a left-sided facial palsy, prompting his presentation to A&E. A CT angiogram and CT cervical spine revealed no evidence of traumatic injury or dissection. An MRI brain and cervical spine was also normal. Over the next 72 hours he developed facial diplegia and weakness at his fingers. He retained all reflexes throughout. Clinically GBS was suspected and nerve conductions studies (NCS) confirmed distal motor slowing with partial motor conduction block with additional neuropraxia in both facial nerves. CSF analysis revealed significantly elevated protein. The facial diplegia improved with 5 days of IVIG. Repeat NCS 13 days after the initial study showed improvement in the compound muscle action potential amplitudes both distally and bifacially. Discussion: The preceding gym injury was incidental and possibly secondary to early symptoms of GBS in this case. This monophasic demyelinating neuropathy is a rare but well-described subtype of GBS.